Comparison of optical and MR‐based tracking. Issue 3 (24th September 2014) - Gumus, Kazim; Keating, Brian; White, Nathan; Andrews‐Shigaki, Brian; Armstrong, Brian; Maclaren, Julian; Zaitsev, Maxim; Dale, Anders; Ernst, Thomas
<x xml:space="preserve">Abstract</x> Purpose The goal of this study was to compare the accuracy of two real‐time motion tracking systems in the MR environment: MR‐based prospective motion correction (PROMO) and optical moiré phase tracking (MPT). Methods Five subjects performed eight predefined head rotations of 8° ± 3° while being simultaneously tracked with PROMO and MPT. Structural images acquired immediately before and after each tracking experiment were realigned with SPM8 to provide a reference measurement. Results Mean signed errors (MSEs) in MPT tracking relative to SPM8 were less than 0.3 mm and 0.2° in all 6 degrees of freedom, and MSEs in PROMO tracking ranged up to 0.2 mm and 0.3°. MPT and PROMO significantly differed from SPM8 in y‐translation and y‐rotation values (P < 0.05). Maximum absolute errors ranged up to 2.8 mm and 2.1° for MPT, and 2.2 mm and 2.9° for PROMO. Conclusion This study presents the first in vivo comparison of MPT and PROMO tracking. Our data show that two methods yielded similar performances (within 1 mm and 1° standard deviation) relative to reference image registration. Tracking errors of both systems were larger than offline tests. Future work is required for further comparison of two methods in vivo with higher precision. Magn Reson Med 74:894–902, 2015. © 2014 Wiley Periodicals, Inc.